(untitled) (Swiss Medical Weekly, 2021)
Colorectal cancer is the third most common cancer worldwide. Half of CRC patients develop liver metastases during the course of the disease, with a 5-year survival rate close to zero in the absence of therapy. Surgical resection remains the only possible curative option, and current guidelines recommend adjuvant chemotherapy, resulting in a 5-year survival rate exceeding 50%. Neoadjuvant systemic therapy is not indicated in cases with simple resection but should be offered to all patients with extensive bilobar disease. Personalised systemic treatment is essential to convert upfront non-resectable lesions to resectable ones. Anatomical resections, non-anatomical resections and two-stage hepatectomies can be performed though open or minimally invasive (laparoscopic or robotic) surgery. The extent of a hepatic resection is limited by the risk of postoperative liver failure due to a too small liver remnant, inflow or outflow obstruction or insufficient biliary drainage. About 75% of patients are diagnosed with non-resectable liver metastases not amenable to a standard upfront resection. In recent years, effective therapeutic approaches have revolutionised liver surgery and new strategies have enabled the conversion of primarily non-resectable metastatic disease for resection. These strategies include oncological and surgical therapies, as well as combinations of the two. From an oncological perspective, colorectal liver metastases may be treated by systemic chemotherapy or immunotherapy, or selective intra-hepatic arterial infusion chemotherapy, depending on the extent of the disease and the mutational status. In surgery, we often apply two-stage strategies using portal vein occlusion, such as portal vein embolisation or ligation, or complex two-stage hepatectomy such as associating liver partition and portal vein ligation for staged hepatectomy. Other additive tools to reach curative resection are tumour ablations (electroporation, microwave or radiofrequency). The role of stereotactic radiation of liver metastases is not yet well defined. Modern radiation techniques, including image guidance, breath hold and gating, were only introduced for a larger patient population in recent years. Therefore, prospective studies with larger patient cohorts are still pending. Over the last decade, liver transplantation has gained increasing attention in selective cases of non-resectable colorectal liver metastases, with promising cohort studies, but definitive recommendations must await the results of ongoing randomised controlled trials. The optimal treatment of patients with colorectal liver metastases requires the timely association of various strategies, and all cases must be discussed at multidisciplinary team conferences. While colorectal liver metastases was a uniformly lethal condition a few decades ago, it has become amenable to curative therapies, with excellent quality of life in many scenarios. This review reports on up-to-date treatment modalities and their combinations in the treatment algorithm of colorectal liver metastases.